Laminated film
The laminated film with alternating thermoplastic resin layers addresses the issue of coloration and performance degradation in humid conditions, ensuring effective heat-shielding and transparency for windows in vehicles and buildings.
Patent Information
- Application Number
- JP2023151916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Existing heat-shielding materials for windows reflect not only heat rays but also visible light, leading to coloration, and their performance is compromised in humid environments, particularly in applications like electric vehicles and advanced housing.
A laminated film with a specific structure of alternately laminated thermoplastic resin layers, each with different refractive indices, achieving high heat-shielding performance by reflecting specific wavelengths while maintaining transparency and stability in humid conditions.
The laminated film provides high heat-shielding performance without coloration, maintaining visibility and stability across various environments, suitable for windows in vehicles and buildings.
Smart Images

Figure 2025044379000001 
Figure 2025044379000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated film that is excellent in heat shielding properties and transparency, and that exhibits these properties even in a humid environment (harsh environment). [Background technology]
[0002] In recent years, various efforts have been made to reduce greenhouse gas emissions as a measure against climate change. For example, there is hope for drastic and large-scale initiatives such as demonstration experiments of smart cities that design entire cities to be environmentally friendly and circulate energy, and companies designing greenhouse gas reductions throughout their entire supply chains. However, these are long-term efforts that involve both the public and private sectors, and there is a widespread demand for more immediate measures.
[0003] As part of this effort, the use of heat-shielding glass, which can reduce the inflow of heat from sunlight and increase air conditioning efficiency, in the windows of vehicles such as cars and trains, and buildings, has attracted attention as a way to reduce greenhouse gas emissions by cutting power consumption.
[0004] Examples of methods for imparting heat insulation properties to window glass include a method in which heat ray absorbing particles are incorporated into glass or an interlayer film used in laminated glass, and heat rays are blocked by the heat ray absorbing particles (e.g., Patent Document 1), a method in which a metal film is formed on the glass surface by sputtering or the like, thereby reflecting and blocking heat rays (e.g., Patent Document 2), a method in which a polymer multilayer laminate film, which is made by alternately laminating polymer layers with different refractive indices, is inserted between the glass and the interlayer film, thereby reflecting and blocking heat rays (e.g., Patent Document 3), and a method in which heat ray absorbing particles are used in addition to interference reflection by a polymer multilayer laminate film to enhance heat insulation performance (e.g., Patent Document 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-17854 A [Patent Document 2] JP2001-310407A [Patent Document 3] International Publication No. 2005 / 040868 [Patent Document 4] Special Publication No. 2010-501458 Summary of the Invention [Problem to be solved by the invention]
[0006] However, although the method using heat ray absorbing particles and the method forming a metal film on the glass surface by sputtering or the like provide higher heat shielding performance than the method using only a polymer multilayer laminate film, they reflect not only heat rays but also visible light, so they are prone to coloring and may not be applicable to the window glass of vehicles or buildings. That is, the methods described in Patent Documents 1, 2, and 4 have the problem that the film is colored.
[0007] In addition, the method described in Patent Document 3, which uses only a polymer multilayer laminate film, has a problem of insufficient heat shielding performance. Furthermore, when these polymer multilayer laminate films are used as heat shielding materials for light control windows, which are increasingly being applied to electric vehicles and advanced housing, a new problem has arisen in that the color changes significantly when condensation forms in a humid environment in the light control state.
[0008] Therefore, an object of the present invention is to provide a laminated film which is free from coloration and exhibits high heat shielding properties under general environments, and which is capable of maintaining its performance even in harsh environments such as humid environments. [Means for solving the problem]
[0009] In order to solve the above problems, a preferred embodiment of the present invention has the following configuration. (1) A laminated film having a laminated structure in which 51 or more layers (A layers) each having a thermoplastic resin A as a main component and a layer (B layers) each having a thermoplastic resin B as a main component different from the thermoplastic resin A are alternately laminated, the thickness being 50 μm or more and 130 μm or less, and having all of the following characteristics 1 to 3. Feature 1: The average reflectance Ra in the wavelength range of 400 to 700 nm is 0.1% or more and 15% or less. Feature 2: The maximum reflectance Rb in the wavelength range of 800 to 850 nm is 1% or more and 30% or less. Feature 3: The average reflectance Rc in the wavelength range of 900 to 1200 nm is 70% or more and 100% or less. (2) The laminate film according to (1), wherein the thermoplastic resin A and the thermoplastic resin B are both polyesters. (3) In the layer A, the layer B, and the resin layer provided on at least one side of the laminate film, the total amount of one or more types of inorganic particles selected from antimony-containing tin oxide, tin-containing indium oxide, tungsten oxide, composite tungsten oxide, and hexaboride is 0.010 g / m 2 The laminate film according to (1) or (2), wherein the thickness is less than 100 nm. (4) The laminate film according to any one of (1) to (3), wherein at least one surface of the film has an 85° gloss of 100 or more. (5) The laminate film according to any one of (1) to (4), having a standard deviation of thickness of 0.01 μm or more and 0.80 μm or less. (6) The laminate film according to any one of (1) to (5), having an absolute value of a thickness change rate after treatment at 90° C. for 30 minutes of 0.20% or less. (7) The laminate film according to any one of (1) to (6), wherein the outermost layers on both sides of the laminate structure are the layers A, the thermoplastic resin A is a crystalline polyester, and the thermoplastic resin B is an amorphous polyester. (8) A laminate obtained by laminating the laminate film according to any one of (1) to (7) to at least one of glass and polycarbonate. (9) A window having at least one of the laminate film according to any one of (1) to (7) and the laminate according to (8). Effect of the Invention
[0010] According to the present invention, it is possible to provide a laminate film that exhibits high heat-shielding performance while being less discolored in humid environments and general environments, and a laminate film that has excellent visibility and heat-shielding properties for a long period of time even in a wide range of usage environments can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The following describes the embodiments of the present invention, but the present invention should not be interpreted as being limited to the embodiments including the following examples, and various modifications are possible within the scope of the invention, as long as the object of the invention can be achieved and the gist of the invention is not deviated from. In addition, for the purpose of simplifying the explanation, some of the explanations are given using an example of a film formed by alternately laminating two types of thermoplastic resins with different optical properties, but the same should be understood when three or more types of thermoplastic resins are used.
[0012] The laminated film of the present invention must be made of a thermoplastic resin. Thermoplastic resins are generally cheaper than thermosetting resins and photocurable resins, and can be easily and continuously formed into a sheet by a known melt extrusion method, making it possible to obtain a laminated film at low cost.
[0013] Furthermore, the laminated film of the present invention must have a laminated structure in which 51 or more layers each of layers (A layers) whose main component is thermoplastic resin A and layers (B layers) whose main component is thermoplastic resin B different from the thermoplastic resin are alternately laminated. "Alternately laminated" here means that the A layers and B layers are laminated in a regular arrangement in the thickness direction, for example, laminated in a regular arrangement such as A(BA)n (n is a natural number representing the number of layers).
[0014] By laminating different thermoplastic resins alternately in this way, it becomes possible to reflect light of a specific wavelength due to the relationship between the difference in refractive index of each layer and the layer thickness. Also, if the number of layers is 50 or less, a high reflectance cannot be obtained over a sufficient band in the infrared region, and sufficient heat shielding performance cannot be obtained.
[0015] From the viewpoint of realizing sufficient heat-shielding performance, the number of layers in the laminated structure is preferably 401 layers or more in total, more preferably 601 layers or more in total. The above-mentioned interference reflection can achieve a higher reflectance for light in a wider wavelength band as the number of layers increases, and a laminated film with high heat-shielding performance can be obtained. In addition, although there is no upper limit to the number of layers in the laminated structure from the viewpoint of heat-shielding performance, as the number of layers increases, the manufacturing cost increases due to the larger size of the manufacturing equipment, and the handleability deteriorates due to the thickness of the laminated film. As a result, for example, when the laminated film is used for laminated glass, a process defect occurs in the process of laminating glass, so that a total of about 1001 layers is practically the practical range.
[0016] The term "thermoplastic resin A and thermoplastic resin B are different" refers to thermoplastic resin A and thermoplastic resin B exhibiting different melting points and / or glass transition temperatures in differential scanning calorimetry (DSC). In the present invention, "exhibiting different melting points" and "exhibiting different glass transition temperatures" means that the melting points and glass transition temperatures differ by 0.1°C or more. The melting points and / or glass transition temperatures more preferably differ by 2°C or more, and more preferably by 5°C or more. When the melting points or glass transition temperatures of thermoplastic resin A and thermoplastic resin B are more significantly different, it becomes possible to more highly control the orientation state of each layer even in the state of a laminated polyester film.
[0017] Depending on the combination of thermoplastic resins, only one of thermoplastic resin A and thermoplastic resin B may exhibit a glass transition temperature or melting point. In this case, the temperature difference cannot be calculated, but the thermoplastic resins are interpreted as being different. On the other hand, using resins that do not exhibit a glass transition temperature or melting point as both thermoplastic resin A and thermoplastic resin B implies that the laminated polyester film cannot be stretched in the manufacturing process, and is not preferable in the present invention, in which a biaxial stretching process is preferable from the viewpoint of reducing adhesion to rolls and clips during stretching.
[0018] Resins with different melting points and glass transition temperatures usually have different optical properties, and therefore, by alternately laminating such resins, it becomes easy to reflect light of a specific wavelength that is determined by the relationship between the difference in refractive index of each layer and the layer thickness.
[0019] Examples of the thermoplastic resins usable as the thermoplastic resins A and B in the laminated film of the present invention include linear polyolefins such as polyethylene, polypropylene, poly(4-methylpentene-1), and polyacetal; alicyclic polyolefins which are obtained by ring-opening metathesis polymerization, addition polymerization, and addition copolymers of norbornenes with other olefins; biodegradable polymers such as polylactic acid and polybutyl succinate; polyamides such as nylon 6, nylon 11, nylon 12, and nylon 66; aramid, polymethyl methacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl butyral, and ethylene vinyl acetate copolymers. Examples of the thermoplastic resins include polyesters such as styrene copolymerized polymethyl methacrylate, polycarbonate, polypropylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, polyethersulfone, polyetheretherketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polyarylate, tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinylidene fluoride. Among these, it is preferable to use polyesters as thermoplastic resins A and B from the viewpoints of strength, heat resistance, transparency, and versatility. The above thermoplastic resins may be used alone, or may be copolymers or mixtures.
[0020] The polyester used for the thermoplastic resins A and B is preferably a polyester obtained by polymerization of a monomer having, as the main constituent, an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid and a diol or an ester-forming derivative thereof.
[0021] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Examples of aliphatic dicarboxylic acids include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof. Among these, terephthalic acid and 2,6-naphthalenedicarboxylic acid, which exhibit a high in-plane average refractive index, are preferred. These acid components may be used alone or in combination of two or more, and may be partially copolymerized with oxyacids such as hydroxybenzoic acid.
[0022] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol. Among these, ethylene glycol is preferably used. These diol components may be used alone or in combination of two or more.
[0023] As the thermoplastic resins A and B in the laminate film of the present invention, it is preferable to use, for example, of the above-mentioned polyesters, polyethylene terephthalate and polymers thereof, polyethylene naphthalate and copolymers thereof, polybutylene terephthalate and copolymers thereof, polybutylene naphthalate and copolymers thereof, polyhexamethylene terephthalate and copolymers thereof, polyhexamethylene naphthalate and copolymers thereof, etc.
[0024] As a preferred combination of thermoplastic resins A and B in the laminated film of the present invention, it is first preferred that the absolute value of the difference in SP value (also called solubility parameter) of each thermoplastic resin is 1.0 or less. If the absolute value of the difference in SP value is 1.0 or less, delamination is unlikely to occur between layers, and it is advantageous in terms of increasing the lamination accuracy. More preferably, it is preferred that polymers having different optical properties contain the same repeating unit. For example, when polyethylene terephthalate is used as one thermoplastic resin, it is preferred that the other thermoplastic resin also contains ethylene terephthalate units from the viewpoint of easily realizing a highly accurate laminated structure. In this way, by combining thermoplastic resins A and B having a common chemical structure, and further increasing the ratio of the common chemical structure, the absolute value of the difference in SP value can be reduced.
[0025] In addition, a preferred combination of thermoplastic resins A and B used in the laminated film of the present invention is one in which the difference in glass transition temperature between the thermoplastic resins is 20° C. or less. By making the difference in glass transition temperature 20° C. or less, the thickness uniformity during film formation of the laminated film is improved, and the variation in heat shielding performance can be suppressed. In addition, problems such as overstretching during molding of the laminated film can be reduced.
[0026] As an example of a combination of resins that satisfies the above conditions, in the laminate film of the present invention, it is preferable that at least one thermoplastic resin layer contains polyethylene terephthalate or polyethylene naphthalate, and at least one other thermoplastic resin layer is a polyester containing spiroglycol carboxylate units. The polyester containing spiroglycol carboxylate units refers to a copolyester copolymerized with spiroglycol, or a homopolyester (the same can be applied to the polyester containing cyclohexanedimethanol carboxylate units described later).
[0027] A polyester containing spiroglycol carboxylate units is preferable because it is less likely to be overstretched during molding and less likely to delaminate due to its small glass transition temperature difference with polyethylene terephthalate and polyethylene naphthalate. From the above viewpoint, it is more preferable that one of the thermoplastic resins A and B is polyethylene terephthalate or polyethylene naphthalate, and the other is a polyester obtained by using spiroglycol and cyclohexanedicarboxylic acid. When a polyester obtained by using spiroglycol and cyclohexanedicarboxylic acid is used, the in-plane refractive index difference with polyethylene terephthalate and polyethylene naphthalate is large, so that a high reflectance is easily obtained. In addition, the glass transition temperature difference with polyethylene terephthalate and polyethylene naphthalate is small, and the adhesiveness is also excellent, so that it is less likely to be overstretched during molding and less likely to delaminate.
[0028] In the laminated film of the present invention, when one of the A layer and the B layer is mainly composed of polyethylene terephthalate or polyethylene naphthalate, these resins may be homopolymers or may be copolymerized with a small amount of other repeating units. Alternatively, the A layer or the B layer may be a single component or may be blended with a small amount of other polyester. In this case, the other layer is preferably mainly composed of a polyester containing cyclohexane dimethanol carboxylate units. Polyester containing cyclohexane dimethanol carboxylate units is preferable because it has a small difference in glass transition temperature from polyethylene terephthalate or polyethylene naphthalate, and is therefore unlikely to be overstretched during molding and unlikely to peel off between layers.
[0029] The polyester containing cyclohexanedimethanol carboxylate units is more preferably an ethylene terephthalate polycondensate or an ethylene naphthalate polycondensate in which the copolymerization amount of cyclohexanedimethanol is 15 mol% or more and 60 mol% or less with respect to 100 mol% of the total glycol components. By adopting such an embodiment, while having high reflectivity, the change in optical properties, particularly due to heating or aging, is small, and peeling between layers is also unlikely to occur. Furthermore, an ethylene terephthalate polycondensate or an ethylene naphthalate polycondensate in which the copolymerization amount of cyclohexanedimethanol is 15 mol% or more and 60 mol% or less is very strongly bonded to polyethylene terephthalate or polyethylene naphthalate. In addition, the cyclohexanedimethanol group exists as a geometric isomer, either a cis isomer or a trans isomer, and as a conformational isomer, either a chair isomer or a boat isomer. Therefore, even when ethylene terephthalate polycondensates or ethylene naphthalate polycondensates are co-stretched with polyethylene terephthalate or polyethylene naphthalate, they are not prone to orientation crystallization, can achieve high reflectance, and show even less change in optical properties due to thermal history, and are also less prone to breakage during film formation.
[0030] In the laminated film of the present invention, it is preferred that the outermost layers on both sides in the film thickness direction are the A layer, the thermoplastic resin A is a crystalline polyester, and the thermoplastic resin B is an amorphous polyester. By having both sides of the laminated film be the A layer which is a crystalline polyester, it is possible to suppress roll adhesion during the film-forming process and blocking during storage as a product roll. In addition, by having the thermoplastic resin B be an amorphous polyester, it is easy to make a laminated film having a desired refractive index difference between the A layer and the B layer and a preferred reflectance performance in each desired wavelength band.
[0031] In the laminated film of the present invention, it is necessary that the average reflectance Ra at wavelengths of 400 nm to 700 nm is 0.1% or more and 15% or less. The laminated film of such an embodiment can be used without problems in applications requiring high transparency.
[0032] In order to obtain such a laminated film, the difference between the optical thicknesses (refractive index of thermoplastic resin × layer thickness) of the two adjacent layers used in the base film can be reduced (preferably equalized) by controlling the layer thickness to a high degree. Ra can also be adjusted by adjusting the number of layers and the amount of inorganic components contained in the surface layer of the laminated film. Specifically, the more the number of layers is increased and the more the amount of inorganic components contained in the surface layer is reduced, the smaller Ra can be. From the viewpoint of transparency, Ra is preferably 0.1% or more and 13% or less, and more preferably 0.1% or more and 11% or less. As Ra decreases, it becomes possible to impart high transparency, but from the viewpoints of productivity and measurement accuracy, the lower limit is 0.1%. Ra can be calculated from the reflectance at each wavelength measured by a known spectrophotometer, and a detailed measurement method will be described later (the same applies to Rc described later).
[0033] In addition, in the laminated film of the present invention, it is necessary that the average reflectance Rc of the laminated film at wavelengths of 900 to 1200 nm is 70% or more and 100% or less. Sunlight has an intensity distribution mainly in the visible light region, and the intensity distribution tends to become smaller as the wavelength increases. However, in order to use it in applications requiring high transparency, it is possible to impart high heat shielding performance to the laminated film by efficiently reflecting light with a wavelength of 900 to 1200 nm (about 18% of the total sunlight intensity) that is slightly longer than the visible light region. From the above viewpoint, Rc is preferably 80% or more and 100% or less, and more preferably Rc is 90% or more and 100% or less.
[0034] Such a laminated film can be realized by increasing the difference in the in-plane refractive index between two or more resins with different optical properties, so in the case of a biaxially stretched film, a layer mainly composed of a crystalline thermoplastic resin and a layer mainly composed of a thermoplastic resin that maintains its amorphous nature during stretching or melts during a heat treatment process may be alternately laminated. Rc can also be increased by increasing the number of layers, adjusting the draft ratio during extrusion to a preferred range described later, reducing the amount of heat ray absorbing components that lead to temperature rise, etc.
[0035] The laminated film of the present invention must have a maximum reflectance Rb of 1% or more and 30% or less at wavelengths of 800 nm to 850 nm. In a humid environment, water droplets that condense and adhere to the glass surface form a layer interface and layer distribution that differ from those when used in a general environment, causing dispersion and refraction of incident light and (interference) reflected light, which changes the reflected wavelength in the laminated film, resulting in a problem of yellow to red coloring. In particular, in a configuration with a low-transmittance base color such as a sunroof with a dimming function, the coloring due to the interference reflection of the laminated film is conspicuous, which limits the range of application of the product.
[0036] Under such circumstances, the inventors have found that light in the above-mentioned 800nm to 850nm wavelength band, which is outside the visible light, is reflected as yellowish to reddish light through the above-mentioned phenomenon caused by water droplets attached to the surface, and by controlling the reflectance in this band to a low level, it is possible to achieve the same level of transparency and heat shielding properties as in general environments even in humid environments. However, conventional polymer multilayer laminate films are designed so that the reflectance changes significantly between the band of wavelengths of 700nm or less and the band of wavelengths of 900nm or more, and such a steep layer thickness gradient that gives a sharp change in reflectance increases the flow rate difference between adjacent layers in the polymer extrusion process, making it unstable, and therefore tends to deviate from the layer thickness distribution design corresponding to the wavelength band. As a result, the reflectance fluctuates in the above-mentioned intermediate wavelength band different from the design by optical calculation, making it difficult to achieve the reflection performance aimed at in the present application.
[0037] Here, as a method for controlling Rb within a preferred range, for example, in a layer thickness band corresponding to a wavelength of 800 nm to 850 nm, a method of setting the layer thickness change rate (thick layer / thin layer) of each adjacent resin layer (same type of polymer) to 1.05 or more and 1.25 or less can be mentioned. By not changing the layer thickness too steeply, the flow rate difference of the polymer described above is reduced and extreme fluctuations are suppressed, and by not changing the layer thickness too slowly, Ra and Rc are also in a preferred range, and the target characteristics can be achieved at the same time. In order to achieve such a rate of change in layer thickness, the machining accuracy of the slit that controls the layer thickness is also important, and it is preferable to set the error range to ±3.0% or less centered on the average deviation from the design. The machining accuracy of the slit can be achieved by adjusting conditions such as increasing the number of machining times and slowing down the machining speed in electric discharge machining and wire electric discharge machining. From the above viewpoint, Rb is more preferably 1% or more and 20% or less, and particularly preferably 1% or more and 15% or less. Rb can be specified from the reflectance at each wavelength measured by a known spectrophotometer, and the measurement method will be described in detail later.
[0038] The laminated film of the present invention must have a thickness of 50 μm or more and 130 μm or less. If the thickness is less than 50 μm, the reflectance is low and sufficient heat shielding performance may not be obtained, and if the thickness is more than 130 μm, the film strength becomes too high, and the processability for building materials and vehicle mounting applications may be insufficient. From the above viewpoint, the thickness of the laminated film is more preferably 70 μm or more and 120 μm or less, and even more preferably 75 μm or more and 110 μm or less.
[0039] The thickness of the laminated film can be measured from a cross-sectional image of the film taken by a transmission electron microscope, etc., and the details of the measurement method will be described later. The thickness of the laminated film can be reduced by increasing the casting speed, reducing the slit width of the die, reducing the amount of resin discharged from the die per unit time, and increasing the stretch ratio.
[0040] The laminate film of the present invention is characterized in that the total amount of one or more inorganic components selected from antimony-containing tin oxide, tin-containing indium oxide, tungsten oxide, composite tungsten oxide, and hexaboride is 0.010 g / m in the layers A and B and in the resin layer provided on at least one side of the laminate film. 2 By setting the content of the inorganic components in each layer within this range, it is possible to provide a high-value-added heat shielding material that is highly transparent to electromagnetic waves and does not block a variety of electromagnetic waves used in sensing and communication. From this viewpoint, the total amount of the inorganic components is preferably less than 0.000 g / m 2 The closer to these components the better, and it is particularly preferred that the content does not include these components.
[0041] The laminated film of the present invention preferably has a standard deviation of thickness of 0.01 μm or more and 0.80 μm or less. The standard deviation of thickness can be calculated from the thickness measured by sampling at any 10 points spaced 100 mm apart from each other, and a detailed measurement method will be described later. By having a standard deviation of thickness of 0.80 μm or less, the reflected wavelength is prevented from shifting to the short wavelength side even at positions where the thickness varies greatly in spots, and it becomes easy to control Rb to the desired range. In addition, the smaller the standard deviation of thickness, the more preferable it is, but in consideration of productivity, the lower limit is practically set to 0.01 μm.
[0042] There is no particular limitation on the method for setting the standard deviation of the thickness of the laminated film within a preferred range, but for example, known methods such as shortening the roll stretching section to improve the thickness uniformity of the biaxially oriented polyester film or subdividing the raw material supply batch to the extruder can be used. In addition, a method of setting the draft ratio (= nozzle lip gap KL (mm) / unstretched film thickness MT (mm)) when extruding a molten polymer from a nozzle to 1.0 to 7.0 is also effective. Generally, the higher the draft ratio, the more advantageous it is for nozzle streaks, but in a multilayer laminated film in which each layer is divided, adhesion due to the ballast effect when extruding from the nozzle may be less likely to occur, and as a result, it may be possible to achieve both good thickness accuracy and suppression of nozzle streaks.
[0043] The laminated film of the present invention preferably has an absolute value of thickness change rate of 0.20% or less after treatment at 90°C for 30 minutes. For example, in an automobile, the surface temperature of the glass in midsummer may reach a maximum of about 90°C, so that the laminated film for automobile use may undergo thickness change due to temperature rise. When such a thickness change occurs, the uniformity of the color tone appears to decrease because the fluctuation conditions are different between the vicinity of the fixed end and the vicinity of the center, and the color change may become easily visible, particularly when the film is exposed to a humid environment and condenses thereafter, which is not preferable. By making the absolute value of the thickness change rate after treatment at 90°C for 30 minutes 0.20% or less, the above-mentioned color change can be suppressed, and from the above viewpoint, the absolute value of the thickness change rate is more preferably 0.10% or less. In addition, since the thickness change rate is preferably as small as possible, the lower limit is not particularly limited, but is 0.01% from the viewpoint of feasibility.
[0044] By setting the absolute value of the thickness change rate after 30 minutes of treatment at 90°C in the above range, such color uniformity is easily maintained even in a harsh environment such as midsummer. The method for setting the absolute value of the thickness change rate of the laminated film after 30 minutes of treatment at 90°C in the preferred range is not particularly limited, but examples include a method of applying tension in a low-temperature process and performing slight stretching. More specifically, in the preheating process of the longitudinal stretching described below, a method of setting the cumulative draw to 0.0020% to 0.0050%, preferably 0.0020% to 0.0040%, etc. can be mentioned. The method for measuring the thickness change rate after 30 minutes of treatment at 90°C will be described later.
[0045] The laminated film of the present invention preferably has an 85° gloss of 100 or more. Although the mechanism is not clear, the high regular reflectivity to light from an angled direction may keep the change in optical path constant even when a water film is formed by condensation under humid conditions, and may reduce yellow to red coloring. From the above viewpoint, the 85° gloss is more preferably 140 or more, and even more preferably 160 or more. The upper limit of the 85° gloss is preferably 250 or less from the viewpoint of the feasibility of the reflective performance of the multilayer film and maintaining the transportability of the film.
[0046] The method for controlling the 85° gloss to the above-mentioned specific range is not particularly limited, but it is preferable to limit the number of protrusions exceeding 400 nm in height to 0.1 / m on the outermost surface of the laminated film. 2 Examples include the following methods. Since such protrusions increase by providing a coating layer that contains particles, the 85° gloss can be reduced, for example, by not providing such a coating layer, or by reducing the amount of particles if such a coating layer is provided. The 85° gloss can be measured according to the method specified in JIS-Z-8741 (1997), and the details of the measurement method are described below.
[0047] Next, a preferred method for producing the laminated film of the present invention will be described below, but the present invention is not limited to the examples. In addition, the laminated structure of the laminated film of the present invention can be produced based on the description in paragraphs
[0053] to
[0063] of JP-A-2007-307893.
[0048] The polyester is prepared in the form of pellets or the like. The pellets are dried in hot air or under vacuum as necessary, and then fed to separate extruders. In the extruder, the resin is heated to above its melting point, and the amount of resin extruded is uniformized by a gear pump or the like, and foreign matter and denatured resin are removed through a filter or the like. These resins are molded into the desired shape by a die and then discharged. The multi-layered sheet discharged from the die is extruded onto a cooling body such as a casting drum, and cooled and solidified to obtain a casting film. At this time, it is preferable to use a wire-shaped, tape-shaped, needle-shaped, or knife-shaped electrode to make the sheet adhere to a cooling body such as a casting drum by electrostatic force and rapidly solidify it. In addition, a method in which air is sprayed from a slit-shaped, spot-shaped, or planar device to make the sheet adhere to a cooling body such as a casting drum and rapidly solidify it, or a method in which the sheet is adhered to a cooling body such as a casting drum and rapidly solidified by a nip roll, is also preferable.
[0049] When preparing a laminated film, two or more extruders are used to send out a plurality of resins from different flow paths, and the resins are sent to a multi-layer lamination device before being extruded from a die onto a cooling body such as a casting drum. As the multi-layer lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but in particular, in order to efficiently obtain the configuration of the laminated film of the present invention, it is preferable to use a feed block that includes at least two or more separate members having a large number of fine slits. When such a feed block is used, the device does not become extremely large, so that there is little foreign matter due to thermal deterioration, and even if the number of layers is extremely large, high-precision lamination is possible. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. In addition, it is also possible to form an arbitrary layer thickness configuration. In addition, in this device, the thickness of each layer can be adjusted by the shape (length, width) of the slit, so that it is easy to achieve an arbitrary layer thickness.
[0050] The molten multilayer laminate thus formed into the desired layer structure is introduced into a die, and a casting film is obtained in the same manner as described above. The casting film thus obtained is preferably biaxially stretched as necessary. Here, biaxial stretching refers to stretching in the longitudinal direction and the width direction. Stretching may be performed in two directions successively, or simultaneously in two directions. Furthermore, re-stretching may be performed in the longitudinal direction and / or the width direction. The longitudinal direction refers to the running direction of the film, and the width direction refers to the direction perpendicular to the longitudinal direction within the film plane.
[0051] First, the case of sequential biaxial stretching will be described. In the case of sequential biaxial stretching, the film is usually stretched in the longitudinal direction and then in the width direction. Here, stretching in the longitudinal direction refers to stretching for giving the film molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage, or may be performed in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of resin, but is usually preferably 2.0 to 15 times, and when polyethylene terephthalate is used as one of the resins constituting the laminated film, it is particularly preferably 2.0 to 7.0 times. In addition, the stretching temperature is preferably the glass transition temperature of the resin with the highest glass transition temperature constituting the laminated film to the glass transition temperature + 100°C.
[0052] In addition, from the viewpoint of suppressing thickness change at the surface temperature of glass exposed to direct sunlight outdoors, the laminated film of the present invention has a cumulative draw by the conveying rolls in the preheating step of longitudinal stretching of preferably 0.0020% to 0.0050%, more preferably 0.0020% to 0.0040%. In this way, by undergoing the process conditions of low temperature and extremely small stretching, low-temperature dimensional stability corresponding to the process temperature can be imparted.
[0053] The uniaxially stretched film thus obtained may be subjected to a surface treatment such as corona treatment, frame treatment, or plasma treatment as necessary, and then may be imparted with properties such as easy slippage, easy adhesion, and antistatic properties by in-line coating.
[0054] The stretching in the width direction refers to stretching for giving the film a width direction orientation, and is usually performed by conveying the uniaxially stretched film while holding both ends in the width direction with a plurality of clips using a tenter, and stretching the film in the width direction. The stretching ratio varies depending on the type of resin, but is usually preferably 2.0 to 15 times, and when polyethylene terephthalate is used as one of the resins constituting the laminated film, it is particularly preferably 2.0 to 7.0 times. The stretching temperature is preferably the glass transition temperature of the resin with the highest glass transition temperature constituting the laminated film to the glass transition temperature + 120°C.
[0055] The biaxially stretched film is preferably heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. By carrying out the heat treatment, the dimensional stability of the laminated film is improved. After the laminated film is heat-treated in this way, it is uniformly cooled slowly, cooled to room temperature, and wound up. If necessary, a relaxation treatment or the like may be used in combination with the heat treatment and slow cooling. In addition, for the laminated film in the present invention, it is particularly preferable that the heat treatment temperature is in the range of the melting point of the laminated film -30°C to the melting point -10°C. When the laminated film is made of a plurality of resins having different melting points, the value of the resin with the highest melting point among them is taken as the melting point of the laminated film. Since polyester crystallizes most immediately before the crystals start to melt, thickness changes in a high-temperature and high-humidity environment can be suppressed.
[0056] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the obtained cast film may be subjected to a surface treatment such as corona treatment, flame treatment, plasma treatment, etc., if necessary, and then may be imparted with functions such as easy slippage, easy adhesion, and antistatic properties by in-line coating.
[0057] Next, the cast film is introduced into a simultaneous biaxial tenter, and conveyed while holding both ends of the film with clips, and stretched simultaneously and / or stepwise in the longitudinal direction and the width direction. The simultaneous biaxial stretching machine may be of the pantograph type, screw type, drive motor type, or linear motor type, but the drive motor type or linear motor type is preferred because it can change the stretching ratio at any desired position and can perform relaxation treatment at any desired position. The stretching ratio varies depending on the type of resin, but is usually preferably 6.0 to 20 times in area, and when polyethylene terephthalate is used as one of the resins constituting the laminated film, the area ratio is particularly preferably 8.0 to 15 times. In addition, the stretching temperature is preferably the glass transition temperature of the resin with the highest glass transition temperature constituting the laminated film to glass transition temperature + 120°C.
[0058] In particular, in the case of simultaneous biaxial stretching, in order to suppress differences in in-plane orientation, it is preferable to make the stretching ratios in the longitudinal direction and the transverse direction nearly equal, and to make the stretching speeds approximately equal as well.
[0059] The biaxially stretched film is preferably subsequently heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. During this heat treatment, it is preferable to instantly relax the film in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone in order to suppress the distribution of the main orientation axis in the width direction. After being heat-treated in this manner, the laminated film obtained is uniformly cooled slowly, cooled to room temperature, and wound up. If necessary, a relaxation treatment may be performed in the longitudinal direction and / or width direction during the period from heat treatment to slow cooling. In this case, it is preferable to instantly relax the film in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone.
[0060] In addition, for the laminated film of the present invention, it is particularly preferable that the heat treatment temperature is in the range of the melting point of the laminated film -30°C to the melting point -10°C. Since polyester undergoes the most crystallization just before the crystals start to melt, thickness changes in a high-temperature, high-humidity environment can be suppressed. When the laminated film is made of a plurality of resins having different melting points, the melting point of the resin with the highest melting point among them is taken as the melting point of the laminated film. Since polyester undergoes the most crystallization just before the crystals start to melt, thickness changes in a high-temperature, high-humidity environment can be suppressed.
[0061] Next, the laminate of the present invention will be described. The laminate of the present invention is formed by laminating the laminate film of the present invention to at least one of glass and polycarbonate. Hereinafter, an example of a process for manufacturing a laminate using the obtained laminate film of the present invention will be described. A transparent substrate such as glass or polycarbonate, an intermediate film typified by polyvinyl butyral cut to a size suitable for the transparent substrate, and the laminate film of the present invention cut to a size suitable for the transparent substrate are arranged in this order, and then heated in a vacuum environment at a temperature of 80 to 120°C for about 0.5 to 1.0 hours for temporary pressure bonding. Next, the laminate is permanently bonded by maintaining the pressure and heating state at a temperature of 100 to 160°C and a pressure of about 1.0 to 1.5 MPa for 0.5 to 1.0 hours. Finally, the intermediate film and the laminate film in the surplus portion outside the transparent substrate are removed to obtain a laminate.
[0062] In addition, when a resin layer is provided on the laminate of the present invention, if the resin layer is a thin film having a thickness of about 10 μm or less, the resin layer can be provided by a method of performing in-line coating or off-line coating. In particular, when the resin used for the resin layer is a resin soluble in a solvent or a thermosetting resin that can be cured in a short time, the resin layer is preferably formed by in-line coating, and when the resin is a thermosetting resin or a photosensitive resin that requires a long time to be cured, the resin layer is preferably formed by off-line coating. On the other hand, when the resin layer is a thick film having a thickness of more than 10 μm, a method of laminating a separately formed film that is the base of the resin layer and a laminated film can also be used in addition to the above method.
[0063] When the laminate of the present invention is subjected to an anti-reflection treatment, it is possible to impart an anti-reflection function by carrying out a coating similar to that described above on the transparent substrate and / or the surface of the laminate film or the surface of the resin layer. In addition, it is also possible to impart an anti-reflection function to the resin layer by laminating a film that is the base of the resin layer and has fine irregularities formed on its surface in advance.
[0064] The laminate of the present invention thus obtained exhibits high heat-shielding performance, but is less colored in a humid environment and in a normal usage environment, and is excellent in visibility and heat-shielding properties in a wide range of usage environments. Therefore, it is particularly suitable as a window for use in automobiles, trains, buildings, etc. That is, the window of the present invention has at least one of the laminate film of the present invention and the laminate of the present invention. EXAMPLES
[0065] The present invention will be described in detail below with reference to examples. The respective property values were measured by the following methods. [Methods for measuring physical properties and evaluating effects] The methods for evaluating the characteristic values and the effects are as follows.
[0066] (1) Number of layers and layer structure The layer structure of the film was identified by observing a sample cut out from a cross section using a microtome with a transmission electron microscope (TEM). Specifically, a transmission electron microscope (TEM) H-7100FA type (manufactured by Hitachi, Ltd.) was used to observe the cross section of the film at a magnification of 40,000 times under conditions of an acceleration voltage of 75 kV, and a cross-sectional photograph was taken to identify the number of layers and the layer structure. In some cases, a dyeing technique using known RuO4, OsO4, etc. was used to obtain high contrast for each layer.
[0067] (2) Calculation method for layer thickness The TEM photograph image obtained in (1) at 40,000 times magnification was captured at an image size of 720 dpi using "CanoScan" (registered trademark) D123U (manufactured by Canon Inc.). The captured image was saved in a compressed image file (JPEG) format on a personal computer, and then the image file was opened using image processing software Image-Pro Plus ver.4 (sold by Planetron Co., Ltd.) to perform image analysis processing. The image analysis processing was performed by reading the relationship between the thickness direction position and the average brightness of the area sandwiched between two lines in the width direction as numerical data in the vertical thick profile mode. After that, using a spreadsheet software ("Excel" (registered trademark) 2003 manufactured by Microsoft Corporation), the data was adopted at sampling step 6 (thinning out 6) for the position (nm) and brightness data, and then numerical processing of a three-point moving average was performed. Furthermore, the data thus obtained, whose brightness changed periodically, was differentiated, and the maximum and minimum values of the differential curve were read using a VBA (Visual Basic for Applications) program, and the layer thickness was calculated by taking the interval between these adjacent values as the layer thickness of one layer. This procedure was carried out for each photograph, and the layer thicknesses of all layers were calculated.
[0068] (3)Reflectance A sample was cut out to 5 cm x 5 cm. A 12° regular reflection attachment P / N134-0104 was attached to a Hitachi spectrophotometer (U-4100 Spectrophotomater), and the reflectance of wavelengths from 250 to 2600 nm at an incident angle of φ = 12 degrees was measured. Measurement conditions: the slit was set to 2 nm (visible) / automatic control (infrared), the gain was set to 2, and the scanning speed was set to 600 nm / min. The light incident surface was set to the transparent substrate side. The reflectance at each wavelength obtained was averaged over the required wavelength band and used as Ra and Rc. The maximum reflectance value from 800 to 850 nm was used as Rb. The measurement surface was selected arbitrarily.
[0069] (4) Total amount of inorganic particles 1g of laminated film 1The particles were poured into 200 ml of N-KOH methanol solution and dissolved by heating under reflux. After dissolution, 200 ml of water was added to the resulting solution, which was then centrifuged to allow the particles to settle, and the supernatant was removed. The particles were washed with more water, and the centrifugation was repeated twice. The particles thus obtained were dried and their mass was measured to calculate the mass fraction of inorganic particles.
[0070] (5) 85° gloss According to the method specified in JIS-Z-8741 (1997), the 85° specular gloss was measured with a Suga Test Instruments digital variable angle glossmeter UGV-5D, N=3, and the average value was used as the 85° gloss. Measurements were performed on both sides, and the larger value was used.
[0071] (6) Thickness of laminated film and its standard deviation Five samples were taken at intervals of 100 mm or more along the surface of the laminated film. Using a scanning electron microscope (Hitachi Field Emission Scanning Electron Microscope (FE-SEM) S-4000), the laminated film was observed at a magnification of 500 to 5,000 times so that the entire thickness of the film was within the field of view, and the thickness of the laminated film was measured from the cross-sectional photographs taken. The same measurement was repeated five times, and the average of the obtained values was taken as the thickness of the laminated film. In addition, the thickness of five points was measured in the same manner from the photographed image of the sample, and the standard deviation was calculated, and the average of the standard deviations obtained for the five samples was adopted as the standard deviation of the thickness of the laminated film.
[0072] (7) Thickness change rate after treatment at 90°C for 30 minutes Five samples of 150 mm x 150 mm size were obtained at intervals of 100 mm or more in the film surface direction. The untreated film thickness of the obtained samples was measured by the method described in (6). Next, each sample was placed on a Bakelite plate and heat-treated at 90°C for 30 minutes while laid flat, and the thickness of the sample after heat treatment was measured in the same manner, and the thickness change rate before and after heat treatment was calculated. The average thickness change rate of each sample was used as the thickness change rate after treatment at 90°C for 30 minutes.
[0073] (8) Transparency The average reflectance Ra of the laminated film in the wavelength range of 400 to 700 nm was evaluated according to the following criteria, with C or higher being considered a pass. A: Ra is 11% or less B: Ra is over 11% and 13% or less C: Ra is more than 13% and less than 15% D:Ra is higher than 15%.
[0074] (9) Heat insulation evaluation The heat shielding performance of the laminated film was evaluated using the following method. Using an XES-155S1 (Minakata Electric Manufacturing Co., Ltd.), the surface temperature rise 30 minutes after irradiation of a black iron plate (size 450 mm x 450 mm, thickness 5 mm) was measured using a FLIRE4 thermography (FLIR Inc.). The distance between the light source and the black acrylic plate was 350 mm, and the light intensity at the position of the black acrylic plate was 1000 W / m 2 The laminated film (size 450mm x 450mm) was placed on top of a black acrylic plate at a position 200mm away from the light source. The temperature rise was evaluated according to the following criteria, with a grade of C or higher being considered a pass. A: The temperature rise of the black acrylic plate was less than 15°C. B: The temperature rise of the black acrylic plate was more than 15°C and less than 20°C. C: The temperature rise of the black acrylic plate was more than 20°C and was 25°C or less. D: The temperature of the black acrylic plate rose above 25°C.
[0075] (10) Transparency when water droplets are attached A black adhesive tape (Nitto Denko No. 5612BN) was attached to one side of the glass laminate, and water was sprayed onto the other side with a spray bottle. The glass laminate was then visually observed at an angle of 70° to the thickness direction, and the color of the water droplets was evaluated according to the following criteria, with a grade of C or higher being considered a pass. A: The water droplets looked colorless and transparent. B: The water droplets appeared slightly reddish. C: The water droplets appeared slightly orange to yellow. D: The water droplets were clearly visible and colored red to yellow.
[0076] (11) Transparency after high-temperature treatment The laminated film was cut into a size of 300 mm x 300 mm and heated in an oven at 90°C for 30 minutes, after which it was processed into a laminate, which was then evaluated in the same manner as described in (8), with a grade of C or higher being deemed to have passed.
[0077] (12) Electromagnetic wave transparency The network analyzer used was a PNAN5250C manufactured by Agilent Technologies. The electromagnetic wave loss in the range of 450 MHz to 15 GHz was measured using the coaxial tube method, and the electromagnetic wave loss in the range of 40 GHz to 110 GHz was measured using the method described in JIS R 1679 (2007) to measure the electromagnetic wave transmittance of the laminated film. The maximum electromagnetic wave loss in the measured frequency ranges of 450 MHz to 15 GHz and 40 GHz to 110 GHz was evaluated according to the following criteria, with a score of B or higher being considered a pass. A: It was less than 0.1 dB. B: More than 0.1 dB and less than 0.5 dB. C: Exceeded 0.5dB.
[0078] (13) Average in-plane refractive index The A layer was measured according to JIS K7142 (2014) A method for the films obtained in the examples and comparative examples described below. As for the B layer, since the resin constituting the B layer in each example and each comparative example is an amorphous resin, an unstretched film was prepared from the resin constituting the B layer, and the refractive index of the B layer was determined. That is, the unstretched film was obtained by melting the resin composition at 280°C in a vented twin-screw extruder, introducing it into a T-die through a gear pump and a filter to form it into a sheet, and then rapidly solidifying it on a casting drum whose surface temperature was kept at 25°C by applying static electricity, thereby obtaining a film with a thickness of 100 μm. The refractive index of the obtained unstretched film was obtained by using an Abbe refractometer 4T (manufactured by Atago Co., Ltd.) according to JIS K7142 (2014) A method to determine the refractive index in MD and TD, and the average value of the obtained values was determined as the in-plane refractive index. The light source used was a sodium D line wavelength of 589 nm. The immersion liquid used was methylene iodide, and the refractive index of the test piece was 1.74.
[0079] (raw materials) The following polyesters were used:
[0080] (Polyester A) 100 parts by mass of dimethyl terephthalate, 57.5 parts by mass of ethylene glycol, 0.03 parts by mass of magnesium acetate dihydrate, and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. The melt was heated to 230°C over 3 hours while stirring, and methanol was distilled off to terminate the transesterification reaction. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.005 parts by mass of phosphoric acid was dissolved in 0.5 parts by mass of ethylene glycol was added. The intrinsic viscosity of the polyester composition at this time was less than 0.2. Thereafter, the polymerization reaction was carried out at a final temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a crystalline polyethylene terephthalate with an intrinsic viscosity of 0.65, which was designated as polyester A. The in-plane average refractive index after filming was 1.66.
[0081] (Polyester B) Amorphous polyethylene terephthalate with an intrinsic viscosity of 0.72, copolymerized with 21 mol% of spiroglycol (SPG) with an intrinsic viscosity (IV) of 0.55 and 24 mol% of cyclohexanedicarboxylic acid (CHDC). The in-plane average refractive index after film formation was 1.55.
[0082] (Polyester C) The amorphous copolymerized polyethylene terephthalate (GN001, manufactured by Eastman Chemical Co.) was copolymerized with 33 mol% of 1,4-cyclohexanedimethanol relative to the glycol component. The intrinsic viscosity (IV) was 0.75, and the in-plane average refractive index after film formation was 1.58.
[0083] Example 1 The prepared polyester A and polyester B were fed into separate single-screw extruders and melt-kneaded at 280°C. Next, each molten resin was extruded and passed through five FSS-type leaf disk filters to remove foreign matter. After that, the resins were metered by a gear pump so that the ratio of optical thickness excluding the polyester thick layer portion was polyester A / polyester B = 1.5, and the resins were joined in a 601-layer lamination device having a total of three slit plates with 201 slits (slit processing accuracy ±2.8%) to form a laminate in which 401 layers were alternately laminated in the thickness direction. The method of forming the laminate was performed according to the description in JP-A-2007-307893, paragraphs
[0053] to
[0056] . Note that since there are layers formed by overlapping layers A, the number of gaps in the slit plate is 601. Here, the slit lengths were all constant, and only the slit gaps were changed to form a gradient structure in the layer thickness distribution. The obtained laminate had 301 layers of polyester A (A layers) and 300 layers of polyester B (B layers), and had a gradient structure in which they were alternately laminated in the thickness direction. The slit gaps were adjusted so that the thick film layers, where the A layers were overlapped on both surface layers of the film and the three slit plates, were 20 times thicker than the adjacent layers. The expansion ratio inside the die, which is the film width direction length of the die lip divided by the film width direction length at the inlet of the die, was set to 2.5. The draft ratio at this time was 3.2.
[0084] The obtained cast film was heated with a group of rolls set at 85°C, and then stretched 3.3 times in the machine direction while rapidly heating both sides of the film with a radiation heater within a stretching section length of 100 mm, and then cooled once. Next, both sides of this uniaxially stretched film were subjected to a corona discharge treatment in air to set the wet tension of the base film to 55 mN / m, and a lamination forming film coating liquid consisting of (polyester with a glass transition temperature of 18°C) / (polyester with a glass transition temperature of 82°C) / silica particles with an average particle size of 140 nm was applied to the treated surface to form a coating layer with excellent transparency, slipperiness, and adhesiveness.
[0085] This uniaxially stretched film was introduced into a tenter, preheated with hot air at 100° C., and then stretched 3.8 times in the transverse direction at a temperature of 110° C. The stretched film was heat-treated in stages with hot air at 230 / 240° C. in the tenter, followed by a 2% relaxation treatment in the width direction under the same temperature conditions, and then rapidly cooled to 100° C. and then a 5% relaxation treatment in the width direction, after which it was taken up to obtain a laminated film.
[0086] The obtained film was then cut to 350 mm x 350 mm, and a PVB sheet (thickness 0.38 mm) cut to the same size as the interlayer film and a 3.2 mm thick glass molded to 300 mm x 300 mm were stacked in the following order: glass, interlayer film, laminated film, interlayer film, glass. These were inserted into a rubber pack, evacuated, and heated at 90°C for 1 hour while being pre-pressed. Furthermore, the film was heated and pressed at 130°C and 13 atm for 0.5 hours in an autoclave for full pressure bonding. Finally, the interlayer film and laminated film protruding from the glass surface were cut off to obtain a glass laminate. The evaluation results of the obtained laminated film and glass laminate are shown in Tables 1 and 2.
[0087] (Examples 2 and 9) A laminate film and a glass laminate were obtained in the same manner as in Example 1, except that the raw materials and production conditions were as shown in Tables 1 and 2. The evaluation results of the obtained laminate film and glass laminate are shown in Tables 1 and 2.
[0088] Example 3 A laminated film and a glass laminate were obtained in the same manner as in Example 1, except that a lamination device with a total of 801 layers using four slit plates with 201 slits (slit processing accuracy of ±2.8%) was used as the lamination device. The evaluation results of the obtained laminated film and glass laminate are shown in Tables 1 and 2.
[0089] (Examples 4 and 8) A laminate film and a glass laminate were obtained in the same manner as in Example 3, except that the raw materials and production conditions were as shown in Tables 1 and 2. The evaluation results of the obtained laminate film and glass laminate are shown in Tables 1 and 2.
[0090] (Examples 5 and 6) A laminate film and a glass laminate were obtained in the same manner as in Example 3, except that the raw materials and manufacturing conditions shown in Tables 1 and 2 were used, both sides of the uniaxially stretched film after longitudinal stretching were subjected to a corona discharge treatment in air to set the wetting tension of the base film to 55 mN / m, and a laminate formation film coating liquid consisting of (polyester with a glass transition temperature of 18°C) / (polyester with a glass transition temperature of 82°C) / silica particles with an average particle size of 50 nm was applied to the treated surface to form a coating layer with excellent transparency, lubricity, and adhesion. The evaluation results of the obtained laminate film and glass laminate are shown in Tables 1 and 2.
[0091] Example 7 DPHA (dipentaerythritol hexaacrylate) and a photoinitiator (BASF Japan "IRGACURE" (registered trademark) 184) were mixed in a mass ratio of 99:1, and the mixture was adjusted to a solid content concentration of 40 mass% with MEK (methyl ethyl ketone) to obtain coating agent A. This coating agent A and cesium tungsten oxide particles Cs with a solid content concentration of 18.5 mass% were mixed. 0.33 The WO3 slurry was mixed at a mass ratio of 2:7 to obtain a coating material for forming a hard coat layer. This coating material was coated on the laminated film of Example 1 using a wire bar coater, and then dried in a hot air oven at 80°C for 2 minutes. The coating material was then irradiated with ultraviolet light at 300 mJ / cm2 using a UV irradiation device. 2The coating was cured by irradiation to obtain a laminated film having a hard coat layer. The obtained laminated film was processed in the same manner as in Example 1 to obtain a glass laminate. The evaluation results of the obtained laminated film and glass laminate are shown in Tables 1 and 2.
[0092] Example 10 Using the laminated film obtained in the same manner as in Example 1, a laminate with polycarbonate was obtained by the following procedure. The laminated film was cut to 350 mm x 350 mm, and a PVB sheet (thickness 0.38 mm) cut to the same size as the intermediate film, and a polycarbonate sheet with a thickness of 3.2 mm molded to 300 mm x 300 mm were laminated in the order of polycarbonate, intermediate film, laminated film, intermediate film, and polycarbonate. These were inserted into a rubber pack, evacuated, and pre-pressed for 1 hour while heating at 90°C. Furthermore, the product was heated and pressed at 160°C and 8 atm for 0.5 hours in an autoclave for main pressing. Finally, the intermediate film and laminated film protruding from the polycarbonate surface were cut to obtain a polycarbonate laminate. The evaluation results of the obtained laminated film and polycarbonate laminate are shown in Tables 1 and 2.
[0093] Comparative Example 1 A laminated film and a glass laminate were obtained in the same manner as in Example 1, except that a 601-layer lamination device having a configuration using a total of three slit plates with 201 slits (slit processing accuracy of ±6.5%) was used. The evaluation results of the obtained laminated film and glass laminate are shown in Tables 1 and 2.
[0094] Comparative Example 2 A laminated film and a glass laminate were obtained in the same manner as in Example 3, except that an 801-layer lamination device having a configuration using a total of four slit plates with 201 slits (slit processing accuracy of ±6.5%) was used. The evaluation results of the obtained laminated film and glass laminate are shown in Tables 1 and 2.
[0095] [Table 1]
[0096] [Table 2] [Industrial Applicability]
[0097] According to the present invention, it is possible to provide a laminate film that exhibits high heat-shielding performance while being less colored in a humid environment and a normal use environment, and a laminate film that is excellent in visibility and heat-shielding properties in a wide range of use environments can be obtained. Since the laminate film of the present invention has the above-mentioned excellent properties, it can be suitably used for windows of buildings as well as windows of vehicles, windshields, sunroofs, rear windows, etc. that require heat-shielding properties.
Claims
1. The laminated film has a laminated structure in which 51 or more layers (A layers) each containing a thermoplastic resin A as a main component and 51 or more layers (B layers) each containing a thermoplastic resin B different from the thermoplastic resin A as a main component are alternately laminated, the thickness is 50 μm or more and 130 μm or less, and the laminated film has all of the following characteristics 1 to 3. Feature 1: The average reflectance Ra in the wavelength range of 400 to 700 nm is 0.1% or more and 15% or less. Feature 2: The maximum reflectance Rb in the wavelength range of 800 to 850 nm is 1% or more and 30% or less. Feature 3: The average reflectance Rc in the wavelength range of 900 to 1200 nm is 70% or more and 100% or less.
2. The laminated film according to claim 1 , wherein the thermoplastic resin A and the thermoplastic resin B are both polyesters.
3. In the layer A, the layer B, and the resin layer provided on at least one side of the laminate film, the total amount of one or more types of inorganic particles selected from antimony-containing tin oxide, tin-containing indium oxide, tungsten oxide, composite tungsten oxide, and hexaboride is 0.010 g / m 2 The laminate film according to claim 1 or 2, wherein the thickness is less than 1 mm.
4. 4. The laminated film according to claim 1, wherein the 85° gloss of at least one surface of the film is 100 or more.
5. The laminated film according to any one of claims 1 to 4, wherein the standard deviation of the thickness is 0.01 µm or more and 0.80 µm or less.
6. 6. The laminated film according to claim 1, wherein the absolute value of the thickness change rate after treatment at 90° C. for 30 minutes is 0.20% or less.
7. The laminated film according to any one of claims 1 to 6, wherein the outermost layers on both sides of the laminated structure are the A layers, the thermoplastic resin A is a crystalline polyester, and the thermoplastic resin B is an amorphous polyester.
8. A laminate comprising the laminate film according to any one of claims 1 to 7 laminated to at least one of glass and polycarbonate.
9. A window comprising at least one of the laminate film according to any one of claims 1 to 7 and the laminate according to claim 8.
Citation Information
Patent Citations
Transparent laminated film
JP2001310407A
Functional film
JP2010017854A
Solar-controlled glazing laminate
JP2010501458A
Near infrared shielding film
WO2005040868A1